Rationale for dapagliflozin administration for the prevention of adverse outcomes in patients with heart failure with reduced ejection fraction. Expert consensus statement - S. N. Tereshchenko; M. V. Shestakova; F. T. Ageev; G. R. Galstyan; A. S. Galyavich; M. G. Glezer; I. V. Zhirov; Yu. A. Karpov; Zh. D. Kobalava; S. T. Matskeplishvili (Российский кардиологический журнал)
Relationships and Activities. The Council of Experts was supported by AstraZeneca.